SQL Antipatterns: Avoiding the Pitfalls of Database Programming - Karwin, Bill (The Pragmatic Bookshelf, 2011)
Each chapter in this book helps you identify, explain, and correct a unique and dangerous antipattern. The four parts of the book group the anti​patterns in terms of logical database design, physical database design, queries, and application development.